THE INFLUENCE OF CUSTOMER EXPERIENCE VALUES ON LOYALTY TO MAKE OVER COSMETIC PRODUCTS IN THE PANTON LABU CITY COMMUNITY, NORTH ACEH REGENCY - Rina Dara; T. Edyansyah; Rusydi; Syamsul Bahri; Muhammad Roni (RADJA PUBLIKA, 2025)
This research was conducted on the loyalty of make over brand cosmetic products in the people of Panton Labu City, North Aceh Regency. Based on the researcher's observations, consumers have long-term loyalty to makeover brand cosmetics, so that consumers feel that they need the product, feel suitable for the product, and will continue to use the product for an unlimited time. This kind of loyalty shows that customers should always feel satisfied with the product they use for longer and accept the value of the customer experience. This customer assessment is divided into three parts, namely: functional value, emotional value, and social value. Based on the description and problems above, the researcher is interested in conducting a study entitled